2014
DOI: 10.2494/photopolymer.27.199
|View full text |Cite
|
Sign up to set email alerts
|

Low Temperature Curable Photo-sensitive Insulator

Abstract: In recent years, novel electronic products have become dramatically smaller and more highly functionalized. Based on these market trends, packaging structures for semiconductors are also required to become smaller, thinner and more complicated. To satisfy various requirements, packaging technologies such as WL-CSP, FO-WLP. 2.5D interposer, 3D-TSV, and so on, are used. For these packaging structures, the photo-sensitive organic materials used for buffer coating, passivation layers, and insulators for re-distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Furthermore, phenolic resin based positive tone resist were reported as photosensitive insulation materials suitable for the low temperature processing below 200 o C of the packaging process [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, phenolic resin based positive tone resist were reported as photosensitive insulation materials suitable for the low temperature processing below 200 o C of the packaging process [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, photosensitive organic materials with low residual stress have been developed as interlayer dielectrics for semiconductor devices [2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Recently, Shoji et al had reported that a photosensitive preimidized polyimide (PI) with low residual stress is developed by introducing special soft segment and utilizing low temperature curable crosslinker [2].…”
Section: Introductionmentioning
confidence: 99%
“…Then we studied the process of making thin and uniform seed layer. We studied liquid-type, negative-tone resist which comprises phenolic resin as base resin, epoxy monomer as photosensitive cross-linker (CL), photo acid generator (PAG), and thermal CL [12][13][14][15][16][17]. We investigated the molecular weight of phenolic-resin to improve lithographic properties.…”
Section: Introductionmentioning
confidence: 99%